One-year mortality of hematopoietic stem cell recipients admitted to an intensive care unit in a dedicated Brazilian cancer center: a retrospective cohort study - Archanjo, Leticia Vicentin Finencio (2023)
BACKGROUND: Hematopoietic stem cell transplantation (HSCT) recipients requiring intensive care unit (ICU) admission early after transplantation have a poor prognosis. However, many studies have only focused on allogeneic HSCT recipients. OBJECTIVES: To describe the characteristics of HSCT recipients admitted to the ICU shortly after transplantation and assess differences in 1-year mortality between autologous and allogeneic HSCT recipients. DESIGN AND SETTING: A single-center retrospective cohort study in a cancer center in Brazil. METHODS: We included all consecutive patients who underwent HSCT less than a year before ICU admission between 2009 and 2018. We collected clinical and demographic data and assessed the 1-year mortality of all patients. The effect of allogeneic HSCT compared with autologous HSCT on 1-year mortality risk was evaluated in an unadjusted model and an adjusted Cox proportional hazard model for age and Sequential Organ Failure Assessment (SOFA) at admission. RESULTS: Of the 942 patients who underwent HSCT during the study period, 83 (8.8%) were included in the study (autologous HSCT = 57 [68.7%], allogeneic HSCT = 26 [31.3%]). At 1 year after ICU admission, 21 (36.8%) and 18 (69.2%) patients who underwent autologous and allogeneic HSCT, respectively, had died. Allogeneic HSCT was associated with increased 1-year mortality (unadjusted hazard ratio, HR = 2.79 [confidence interval, CI, 95%, 1.48–5.26]; adjusted HR = 2.62 [CI 95%, 1.29–5.31]). CONCLUSION: Allogeneic HSCT recipients admitted to the ICU had higher short- and long-term mortality rates than autologous HSCT recipients, even after adjusting for age and severity at ICU admission.